2019
DOI: 10.3390/jcdd6030032
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Exercise Workload Progression Across 36 Sessions of Cardiac Rehabilitation on Functional Capacity

Abstract: Defining time frames throughout cardiac rehabilitation (CR) to progress exercise workloads may lead to improve functional capacity outcomes. The purpose of this study was to investigate the role of exercise progression on functional capacity among cardiac patients enrolled in CR. This was a retrospective database analysis study. Extracted data included: Demographic, functional capacity (in METs), and exercise intensity during exercise sessions 2, 12, 24, and 36 of CR from 150 patients who completed a 36-sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The CORE training session should last at least 60 min (warm-up, plateau, and cool-down), at least three times a week, including aerobic and resistance exercises 50 and prescribing an exercise intensity using the usual CR methods (from indirect ones, based on a scale of subjective perception of fatigue to direct ones based on the calculation of training heart rates through physical exercise or cardiopulmonary tests). 51 Generally, a gradual approach with a progressive increase in workload is preferred, especially in patients with metastases, osteoporosis, or recent surgical interventions. The protocol should last for at least 24 sessions, but in subjects with compromised contractile function, it is reasonable to reach 36 sessions in total.…”
Section: Core: the Training Programmementioning
confidence: 99%
See 1 more Smart Citation
“…The CORE training session should last at least 60 min (warm-up, plateau, and cool-down), at least three times a week, including aerobic and resistance exercises 50 and prescribing an exercise intensity using the usual CR methods (from indirect ones, based on a scale of subjective perception of fatigue to direct ones based on the calculation of training heart rates through physical exercise or cardiopulmonary tests). 51 Generally, a gradual approach with a progressive increase in workload is preferred, especially in patients with metastases, osteoporosis, or recent surgical interventions. The protocol should last for at least 24 sessions, but in subjects with compromised contractile function, it is reasonable to reach 36 sessions in total.…”
Section: Core: the Training Programmementioning
confidence: 99%
“…Moreover, it is known, at least for the CR, that the improvement in functional capacity is progressive and constant with the increase in the number of sessions at least until the 36th session. 51 …”
Section: Core: the Training Programmementioning
confidence: 99%
“…In addition, coronary artery disease patients, who exercise at or below 3.5 METs upon completion of CR were characterized as a high-risk group with 3-year cardiac event rates above 18% [23]. Furthermore, our group recently reported that an increase in treadmill exercise workloads between CR sessions 12 to 24 and 24 to 36 predicted functional capacity improvements of 0.50 to 0.80 METs, respectively in a diverse group of patients [24]. Collectively this suggests it is of critical importance that CVD patients are progressed toward achieving higher exercise workloads throughout their CR program.…”
Section: Exercise Progression Techniquesmentioning
confidence: 99%